Help desk support models : a thesis presented in partial fulfilment of the requirements for the degree of Master of Information Systems at Massey University, Palmerston North, New Zealand - Yap, Dora A Y (Massey University, 2005)
In the early 1980s some clerical workers, engineers and a few so-called "leading edge" managers and professionals started to use computers in their daily jobs. This is in contrast to today's office environment where the computer is the standard desktop equipment in most offices. In response to the increasing demand for support of this desktop equipment, Help Desks were formed. Help Desks have since become an important function of the organisation and have been the subject of much research on topics such as the ratio of Help Desk staff to users, the prescriptions and functions of Help Desks, and user satisfaction with Help Desk support. This research investigates the efficiency of the Second Level Help Desk Support Models, and user satisfaction rates for these models. This study focused on surveying a large financial organisation in New Zealand in order to find out if the In-house Help Desk Support Model has a higher level of user satisfaction or is more efficient than the Outsourced Help Desk Support Model. Overall, the results of the survey showed that there is no difference between the In-house and the Outsourced Help Desk Support Model in end user satisfaction and efficiency. Both statistical and qualitative studies supported these conclusions. As this survey was exploratory in nature, there is opportunity for researchers to explore and expand this research to cover a wider group of end users across different industry types, ranging from large corporations to small or medium-sized companies.
Keywords: Customer services; Computer industry; Computer technical support; Evaluation; New Zealand Call Centers